Green Synthesis of Luminescent Gold-Zinc Oxide Nanocomposites: Cell Imaging and Visible Light–Induced Dye Degradation - Bharti, Kanika; Lone, Shahbaz Ahmad; Singh, Ankita; Nathani, Sandip; Roy, Partha; Sadhu, Kalyan K. (Frontiers in Chemistry, 2021)
Green synthesis of gold-zinc oxide (Au-ZnO) nanocomposite was successfully attempted in organic solvent free condition at room temperature. Prolong stirring of the reaction mixture introduced crystallinity in the ZnO phase of Au-ZnO nanocomposites. Luminescence property in these crystalline Au-ZnO nanocomposites was observed due to in situ embedding of 5-6 nm diameters gold nanoparticles (AuNP) on the surface. This efficient strategy involved the reduction of Au(III) by Zn(0) powder in aqueous medium, where sodium citrate (NaCt) was stabilizing agent. Reaction time and variation of reagent concentrations were investigated to control Au:Zn ratio within the nanocomposites. The reaction with less amount of NaCt for long duration resulted Au-ZnO/Zn(OH)2 nanocomposite. X-ray photoelectron spectroscopy (XPS) confirmed the formation of Zn(OH)2 and ZnO in the same nanocomposite. These nanocomposites were reconnoitered as bioimaging materials in human cells and applied for visible light induced photodegradation of rhodamine-B dye.